2020
DOI: 10.1038/s41467-020-16557-2
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genomes from northern China suggest links between subsistence changes and human migration

Abstract: Northern China harbored the world's earliest complex societies based on millet farming, in two major centers in the Yellow (YR) and West Liao (WLR) River basins. Until now, their genetic histories have remained largely unknown. Here we present 55 ancient genomes dating to 7500-1700 BP from the YR, WLR, and Amur River (AR) regions. Contrary to the genetic stability in the AR, the YR and WLR genetic profiles substantially changed over time. The YR populations show a monotonic increase over time in their genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
262
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 183 publications
(277 citation statements)
references
References 53 publications
13
262
2
Order By: Relevance
“…We also identified the subtle genetic differences of these Neolithic to Iron Age individuals from northern (Ning, et al 2020). Here, we observed the late Neolithic populations in the southern cluster was localized between Patterns of genetic relationship revealed from the top two components (extracting 43% variation: PC1: 31.04% and PC2: 11.86%) revealed a genomic affinity between modern Tibetans, ancient Nepal populations, and modern/ancient East Asians and Siberians.…”
Section: Genome-wide Data Of Both Modern and Ancient Tibetans Showedmentioning
confidence: 70%
See 4 more Smart Citations
“…We also identified the subtle genetic differences of these Neolithic to Iron Age individuals from northern (Ning, et al 2020). Here, we observed the late Neolithic populations in the southern cluster was localized between Patterns of genetic relationship revealed from the top two components (extracting 43% variation: PC1: 31.04% and PC2: 11.86%) revealed a genomic affinity between modern Tibetans, ancient Nepal populations, and modern/ancient East Asians and Siberians.…”
Section: Genome-wide Data Of Both Modern and Ancient Tibetans Showedmentioning
confidence: 70%
“…More and more ancient DNA studies from the surrounding of East Asia have been conducted and reported the population dynamics in Southeast Asia (Lipson, Cheronet, et al 2018;McColl, et al 2018) and South Siberia or Eurasia's Eastern Steppe (Lazaridis, et al 2014;Raghavan, et al 2014;Mathieson, et al 2015;Damgaard, et al 2018;Sikora, et al 2019), but lack in China. Fortunately, six ancient DNA studies from China (Yang, et al 2017;Ning, et al 2019;Ning, et al 2020;Wang, Yeh, et al 2020; have been recently published to elucidate the prehistory of East Asian independently with 161 Paleolithic to historic (ranging from 40,000 ybp to 300 ybp). Yang et al sequenced 40,000-year-old Tianyuan people from Beijing and found the early Asian population structures existed before the divergence between East Asian and Native American and the peopling of America by anatomically modern human populations (Yang, et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations